AR Media Development to Improve Cultural Literacy and Language Skills in Elementary Schools - Syibli Maufur; Ade Aspandi; Abdus Salam (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to develop Augmented Reality (AR)-based learning media on cultural diversity materials as an innovative product to strengthen cultural literacy and language skills among Madrasah Ibtidaiyah (MI) students in Cirebon City. Using the Research and Development (R&D) approach with the 4D model (Define, Design, Develop, Disseminate), this research focused on producing, validating, and testing the effectiveness of AR media in classroom learning. Data were obtained through literacy and language skill assessments, observations, questionnaires, and interviews. Quantitative data were analyzed statistically, while qualitative data were analyzed descriptively. The results show that the developed AR-based media is valid, practical, and effective in enhancing students’ cultural literacy and language performance. Statistical tests indicate significant differences in student outcomes before and after the use of AR media (sig = 0.00 < 0.05). The interactive nature of AR helped students connect cultural content with language expression more meaningfully. The study concludes that AR-based learning media serves as a creative educational innovation to improve literacy and communication skills while fostering appreciation of Indonesia’s cultural diversity among MI students.